2021
DOI: 10.21203/rs.3.rs-464371/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison Between Healthcare Professionals And The General Population On Parameters Related To Natural Remedies Used During The COVID-19 Pandemic

Abstract: Introduction: Herbal medicine is a common method for symptom relief and treatment because of its ample availability and lack of regulation on its prescription. However, herbal use is associated with adverse effects, drug interaction, and sometimes life-threatening complications. During the coronavirus disease (COVID-19) pandemic, people shifted toward herbs when modern medical field failed to discover a treatment or immunization early in the course of the disease. Based on expert consensus, herbal medicine was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In a study with similar results to our study, it was determined that 17.2% of nursing students consumed yogurt and kefir to protect themselves from COVID-19 disease [6]. In another study conducted with healthcare professionals, it was found that 9% of the participants believed that kefir protects from COVID-19 [4].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In a study with similar results to our study, it was determined that 17.2% of nursing students consumed yogurt and kefir to protect themselves from COVID-19 disease [6]. In another study conducted with healthcare professionals, it was found that 9% of the participants believed that kefir protects from COVID-19 [4].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, in a study conducted with nursing students in Turkey, it was reported that 57.7% of the participants consumed lemon to prevent COVID-19 [6]. In a study investigating the use of herbal products in the general population and healthcare personnel during the COVID-19 pandemic, it was reported that both healthcare personnel and the general population took vitamin C supplements or that the consumption of citrus fruits containing vitamin C such as lemons and oranges is common [4]. In another study evaluating the nutritional habits of adults after the COVID-19 epidemic, it was determined that almost half of the participants (50.4%) started to take vitamin C as a supplement [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations